PENGARUH PEMBAGIAN INFORMASI MNEGGUNAKAN MEDIA AUDIO VISUAL TERHADAP PEMAHAMAN REMAJA PUTRI TENTANG SADARI DI SMA 8 BATAM TAHUN 2017 - Permatasari, Yulia; Aryaneta, Yenni (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2018)
Cancer is one of the non-communicable diseases that is a health problem in the world and Indonesia. The purpose of this study is to determine the provision of information using audio visual media to understanding teenage daughter about BSE. this research is a research with pretest-posstest one group design rancanagan. This research was conducted on February-june 2017 at SMA Negeri 8 Batam. The population in this study were students of class X and XI SMA Negeri 8 Batam as many as 897 students with a sample of 120 people. the result of the research is known to know the mean value of the understanding of adolescent princess after given information is equal to 8.53 and mean value of the understanding of adolescent daughter after given information is equal to 17,515 so mean understanding of young woman before and after giving information is experiencing of ebear 8.62. the conclusion of this study found that giving informsi can have a significant influence on improving understanding of teenage daughter about BSE. Advice for educational institutions is expected school institutions collaborate with health workers can be more disseminating ptogram giving information or giving counseling so that information is spread evenly For all young women